The Plant Cell Wall: A Complex and Dynamic Structure As Revealed by the Responses of Genes under Stress Conditions - Houston, Kelly; Tucker, Matthew R.; Chowdhury, Jamil; Shirley, Neil; Little, Alan (Frontiers in Plant Science, 2016)
The plant cell wall has a diversity of functions. It provides a structural framework to support plant growth and acts as the first line of defence when the plant encounters pathogens. The cell wall must also retain some flexibility, such that when subjected to developmental, biotic or abiotic stimuli it can be rapidly remodelled in response. Genes encoding enzymes capable of synthesising or hydrolysing components of the plant cell wall show differential expression when subjected to different stresses, suggesting they may facilitate stress tolerance through changes in cell wall composition. In this review we summarise recent genetic and transcriptomic data from the literature supporting a role for specific cell wall-related genes in stress responses, in both dicot and monocot systems. These studies highlight that the molecular signatures of cell wall modification are often complex and dynamic, with multiple genes appearing to respond to a given stimulus. Despite this, comparisons between publically available datasets indicate that in many instances cell wall-related genes respond similarly to different pathogens and abiotic stresses, even across the monocot-dicot boundary. We propose that the emerging picture of cell wall remodelling during stress is one that utilises a common toolkit of cell wall-related genes, multiple modifications to cell wall structure, and a defined set of stress-responsive transcription factors that regulate them.